PARENTAL REGULATION OF INTERNET USE: ISSUES OF CONTROL, CENSORSHIP AND CYBERBULLYING - Moodley, Padhma; Singh, Jesika Rachel (Mousaion: South African Journal of Information Studies, 2016)
The attraction of the internet continues to grow, mobilising the attention of many users, and impressing especially adolescents globally. Whilst the internet has provided adolescents with many benefits, such as academic support; cross- cultural interactions; social support; and exposure to the world at large, there are serious risks associated with the internet. The parents’ role in this regard becomes pivotal in ensuring the safety of their children. The mechanisms used by parents in controlling their children’s use and access to the internet were the focus of this study. For this reason, the study aimed to determine the role parents play in regulating their adolescent children’s use of and access to the internet and how issues of control, censorship and cyberbullying are addressed. The study was based on Baumrind’s (in Grobman 2008) parenting styles which formed the theoretical framework. A quantitative approach was used to gauge the responses of parents who have adolescent children. Through convenience sampling, the respondents were selected to answer a questionnaire made up of closed-ended questions. The key findings that emerged from the study revealed that parents applied the permissive style of parenting when it came to male adolescents, whilst they applied the authoritative style of parenting to female adolescents.